Educación musical y sistema educativo chileno (Educational Perspectives Magazine (REPED), 2022)
In the middle of century XIX, José Zapiola, a Chilean musical visionary, obtained the beginning of the presence of music in the Chilean educative system, through the company/signature of minister San Fuentes, so that the subjet of Level Song in the 27 Esta ponencia se genera en el marco del proyecto DIUMCE, “FIMAP 02-08”, Representaciones e imaginarios sociales del profesor secundario y sus especialidades científico-humanistas (1889- 2009.) schools of teachers of the rising republic was created. That was the beginning of the scholastic subjet, “Musical Education”, today “Musical Arts”, that have happened through múltiple reforms, profits and difficulties. Today we were in a somewhat difficult situation and a great paradox: several universities are offering the race ofpedagogy in music but to the new professors work is costing to find a space them in the scholastic system. The reason: the directors of the schools are privileging others knowledge. It is not the only problem. At the present time, any professional who knows music could give the subjet. That is to say, there are more professors of music and there is sufficient no labor field because music is not of high-priority curricular interest. It could think that it is an impasse, nevertheless, same the problematic ones can be transformed into opportunities. Studying them can be a way to understand the relation musical education/Chilean educative system. It is the objective of the following reflection.
Keywords: Musical Education, Musical Arts, Educative Reform, Scholastic System